Answer :


Given that,


In Δ PQR


PQ = QR


And,


L, M, and N are the mid points of PQ, QR and RP respectively


To prove: LM = MN


Construction: Join L and M, M and N and N and L


Proof: We have,


PL = LQ, QM = MR and RN = NP


Since, L, M and N are mid points of PQ, QR and RP respectively.


And, also PQ = QR


PL = LQ = QM = MR = = (i)


Using mid-point theorem, we have


MN PQ


And,


MN = PQ = MN = PL = LQ (ii)


Similarly, we have


LN QR


And,


LN = QR = LN = QM = MR (iii)


From equations (i), (ii) and (ii), we have


PL = LQ = QM = MR = MN = LN


Therefore, LN = MN


Hence, proved


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove that the anRS Aggarwal & V Aggarwal - Mathematics

If the sides of aRD Sharma - Mathematics

D is any point onNCERT Mathematics Exemplar

In a triangle RD Sharma - Mathematics

In Δ ABCRD Sharma - Mathematics

In Δ PQRRD Sharma - Mathematics

<span lang="EN-USRS Aggarwal & V Aggarwal - Mathematics

Prove that the peRD Sharma - Mathematics

In Fig. 10.25, <iRD Sharma - Mathematics

In a <span lang="RD Sharma - Mathematics